Community Participation in Shaping the Religious Character of Mosque Youth in Asahan Regency as Informal Islamic Education - Ahyar, Saiful; Nahar, Syamsu; Arsyad, Junaidi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to analyze: Community participation in shaping the character of mosque youth, in the form of strategic steps, supporting and inhibiting factors, efforts to overcome obstacles for mosque youth in Asahan Regency. This research uses a qualitative method with a phenomenological approach, data collection techniques using observation, interviews and document study, and techniques for ensuring the validity of the data using credibility, transferability, dependability and comfirmability. The results of this research are that; The similarity of views in developing the religious character of teenagers is not optimal, the pattern of fostering the religious character of teenagers includes, involving teenagers in community activities, controlling teenagers in destroying mosques, coaching in the form of economic independence for teenagers such as selling to break the fast.The conclusion of this research is that parents do not agree with mosque teenagers, the optimization of the approach has not been achieved, for teenagers themselves who like to get together.